Mediation of executive functions in the relationship between motor skills and psychosocial health in preschool children - Sen Li; Yang Song; Qingwen Zhang; Zhen Wang (Journal of Exercise Science & Fitness, 2025)
Purpose: Early motor skills develop alongside executive functions and psychosocial health. However, the interaction between these elements in early childhood is not well-studied. This study aimed to examine whether executive functions mediate the relationship between motor skills and psychosocial health. Methods: A total of 452 children (mean age = 6.14 ± 0.29 years, 48.9 % female) were included in this cross-sectional study. The Movement Assessment Battery for Children-Second Edition (MABC-2) was used to assess motor skills. Executive functions were measured using the Go/No-Go Test, Dimensional Change Card Sort Test, and List Sorting Working Memory Test from the Early Years Toolbox (ages 3–7). Social skills and problem behaviors were assessed using the preschool version of the Social Skills Improvement System Rating Scale (SSIS-RS). Structural equation modeling (SEM) with maximum likelihood estimation was employed to examine the mediating role of executive functions. Results: Gross motor skills were positively associated with inhibition (β = 0.41, p < 0.01), shifting (β = 0.20, p < 0.01), working memory (β = 0.30, p < 0.01), social skills (β = 0.50, p < 0.05), and negatively associated with problem behaviors (β = −0.23, p < 0.05). Inhibition (β = 0.107, p < 0.001) and shifting (β = −0.018, p < 0.05) mediated the relationship between gross motor skills and social skills. Additionally, inhibition (β = −0.086, p < 0.001) and shifting (β = 0.019, p < 0.05) mediated the relationship between gross motor skills and problem behaviors. Fine motor skills were positively associated with inhibition (β = 0.35, p < 0.01), shifting (β = 0.16, p < 0.01), and working memory (β = 0.21, p < 0.01), but not significantly related to social skills (β = 0.08, p > 0.05) or problem behaviors (β = 0, p > 0.05). Inhibition (β = 0.144, p = 0.001) mediated the relationship between fine motor skills and social skills, while both inhibition (β = −0.102, p = 0.001) and shifting (β = 0.014, p = 0.041) mediated the relationship between fine motor skills and problem behaviors. Conclusion: Executive functions significantly mediate the association between motor skills and psychosocial health in preschool children. Future experimental studies are required to examine causality in young children.